Psychomotor Profile and Language in Schooled Children with mixed Specific Language Impairment - Allende Valenzuela, Tamara; Wrann Reinike, Beatriz; Quezada Gaponov, Camilo (Revista de Investigación en Logopedia, 2021)
Diagnosing Specific language Impairment (SLI) is usually done by speech therapists who resort exclusively to their own professional knowledge as clinician, with not much input from other fields. It has been shown that children’s development is a complex process which may be impacted by different factors which influence each other and play a role in how skills, abilities, and capabilities evolve during childhood. Since dimensions are interwoven, it might be of interest to inspect the possible relation between the pathological acquisition of language and some other developmental aspects. In this study, the psychomotor profile of 22 children with mixed SLI was observed (age range 5.0 – 7.11). They all attended a public school in Santiago, Chile. Scores obtained on psychomotor measures were correlated with some linguistic variables: vocabulary, receptive grammar, expressive grammar and phonology. Results show that the observed children with SLI had an either normal or a dyspraxic profile, with no difference per age group. All inspected psychomotor factors correlated with one or more linguistic variable, except for laterality, which correlated with no linguistic variable. Vocabulary was the language variable that more frequently correlated with psychomotor factors. Children scored the lowest on three psychomotor factors: notion of body, spatiotemporal structuring and fine-grained praxia.
Keywords: language development; specific language impairment; globality; psychomotor profile; psychomotor factors